Effects of Ascorbic Acid Injection in Incubated Eggs Submitted to Heat Stress on Incubation Parameters and Chick Quality - Sgavioli, S.; Matos Junior, J. B. [UNESP]; Borges, L. L. [UNESP]; Praes, M. F. F. M.; Morita, V. S. [UNESP]; Zanirato, G. L. [UNESP]; Garcia, R. G.; Boleli, I. C. [UNESP] (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2015)
Dose-dependent positive effects on hatchability and hatchling weight have been attributed to ascorbic acid (AA) when eggs were submitted or not to intermittent heat stress during incubation. Fertile breeder (Cobb (R)) eggs were used to determine if the pre-incubation injection of AA in ovo affects the incubation and hatchling quality of egg incubated under thermoneutral or intermittent heat stress conditions. Eggs were not injected or injected with 0, 2,4, or 6% AA/100 mu L water and incubated at continuous thermoneutral (37.5 degrees C) or hot (39.0 degrees C) temperature. Eggshell temperature (EST) increased in the second half of the incubation period in all experimental groups. The EST of non-injected eggs and of those injected with water was higher when incubated at 39 degrees C than at 37.5 degrees C, but EST was not different among eggs injected with AA. Egg mass loss and eggshell conductance were higher in the eggs incubated at 39 degrees C than at 37.5 degrees C. Hatchability was lower in the eggs injected with AA. Liver and yolk sac weights were higher, whereas heart and liver weights were lower in hatchlings from eggs incubated at 39 degrees C; however, hatchling weight was not affected by incubation temperature. The results showed that AA doses affected egg conductive heat loss and hatchability, and that they did not minimize the effects of high incubation temperature on liver and heart development.
Keywords: Conductance; hatchability; egg mass loss; hatchling weight; eggshell temperature